Occlusion of functional high-volume intra-atrial shunts in older patients after embolic stroke of undetermined source - Schrader, Helene; Boldt, Leif-Hendrik; Parwani, Abdul S.; Blaschke, Florian; Wiedenhofer, Julia M.; Trippel, Tobias D.; Hindricks, Gerhard; Starck, Christoph; Dreger, Henryk; Sherif, Mohammad; Primessnig, Uwe (Frontiers in Cardiovascular Medicine, 2024)
Background: Intra-atrial shunts are associated with an elevated risk for embolic stroke of undetermined source (ESUS). Percutaneous occluder implantation is recommended as secondary prevention in younger patients. This study aims to compare the outcome after shunt occlusion between younger and older patients with a history of presumed paradox embolism and evaluate the impact of high-volume shunting in an elderly population.We performed a single-centre, retrospective, observational study and included 187 patients, that underwent interventional percutaneous PFO or ASD occlusion between 2013 and 2023 at our centre.Results: Mean age was 51.8±11.8 years with 76 patients in the age group < 50 years and 111 patients in age group > 50 years. Older patients had more cardiovascular risk factors. Presence of atrial septum aneurysm or large shunting was evenly distributed (ASA 26.3% vs. 28.8%, p=0.833, mean shunt defect size 6.67 vs. 7.23 mm, p=0.151). There were no differences in procedural or intrahospital complications. Event rate during 6-month follow up was low.Recurrence of arterial embolism occurred in 1.6% of the younger and 3.8% of the older patients (p=0.817). Comparing high volume shunts (defect size > 10 mm or passage > 20 bubbles during bubble study) with low volume shunts in this elderly cohort with a mean age > 50 years, showed no significant difference regarding the outcome. There was a statistically non-significant trend towards a higher rate of residual shunt at the end of the procedure in the high volume shunt group (2.9% vs. 9.8%, p=0.0894). This difference could not be seen at the 6 months follow up anymore (14.5 vs. 12.1%, p=0.628). Two unsuccessful implantation attempts were reported in the high volume shunt group, while none was observed in the low volume shunt group (p=0.372). No intervention related deaths occurred in this patient cohort during follow up.Occlusion of relevant, intra-atrial shunting is a safe and effective option for secondary prevention of cryptogenic embolism in patients >50 years of age. Beneficial outcome was irrespective of a high volume shunting before implantation.